Penerapan Ice Breaking dalam Kegiatan Mata Kuliah Bermain dan Permainan AUD pada Mahasiswa Strata I UIN Sunan Kalijaga.: Application of Ice Breaking in Concentration Lecture Activities for Playing and Games Subjects for Level I Students at UIN Sunan Kalijaga. - Maratun Sholihah; Hibana; Na'imah (Indonesian Journal of Early Childhood: Jurnal Dunia Anak Usia Dini, 2024)
Learning is a complex activity. Learning is not just conveying messages but is also a professional activity that requires teachers to use basic pedagogical skills in an integrated manner in creating effective situations. Ice Breaking is a simple, light and concise game or activity that functions to change the atmosphere of freezing, stiffness, boredom or sleepiness in lecture activities. The research method in this article is a descriptive qualitative method carried out at UIN Sunan Kalijaga on third semester students of the PIAUD study program. The results of the research showed that the lecturer implemented ice breaking to re-optimize the class situation at the beginning of the delivery of the material which did not seem conducive because the students started to feel sleepy, bored and not concentrating on the lecturer's explanation in front of the class. So use various types of icebreakers, namely 1). Types of shouts 2). Interactive clap type 3). Types of games and games and the last one 4). Types of audio visuals that can be delivered at the beginning or closing activities. This is an effective way to restore students' learning motivation so that the class becomes active and conducive.   ABSTRAK Pembelajaran merupakan suatu kegiatan yang komplek. Pembelajaran bukan hanya sekedar menyampaikan pesan tetapi juga merupakan kegiatan profesional yang menuntut guru untuk menggunakan keterampilan pedagogis dasar secara terpadu dalam menciptakan situasi yang efektif. Ice Breaking merupakan permainan atau kegiatan yang sederhana, ringan dan ringkas yang berfungsi untuk mengubah suasana kebekuan, kekakuan rasa bosan atau mengantuk dalam kegiatan perkuliahan. Metode penelitian pada artikel ini metode kualitatif deksriptif yang dilakukan di UIN Sunan Kalijaga pada mahasiswa semester III prodi PIAUD. Hasil dari penelitian menunjukkan bahwa Dosen mengimplementasikan ice breaking dilakukan untuk mengoptimalkan kembali situasi kelas pada awal penyampaian materi terlihat tidak kondusif karena mahasiswa mulai mengantuk, bosan, dan tidak konsentrasi pada penjelasan Dosen didepan kelas. Maka menggunakan ice breaking dengan berbagai jenis yaitu Jenis yel-yel Jenis tepuk interaktif. Jenis games maupun permainan dan yang terahir. Jenis audio visual yang bisa disampaikan pada kegiatan awal, maupun kegiatan penutup. menjadi hal yang efektif untuk mengembalikkan motivasi belajar mahasiswa sehingga kelas menjadi aktif dan kondusif.